On the Question of Islamization of Ugrian Population in Western Siberia from the sixteenth to early eighteenth centuries and Some Aspects of Study of This Process - Maslyuzhenko D.N.; Samigulov G.Kh. (Золотоордынское обозрение)
Research objectives: The reconstruction of the features of Islamization of the Ugrian population in Western Siberia from the sixteenth to early eighteenth centuries and some controversial points in the research of this process. Research materials: The present study was based on the analysis of published sources: chronicles, memoirs, and archaeological as well as historiographical data. Results and novelty of the research: The penetration of world religions, including Islam, into the taiga and tundra zone of Western Siberia in the late Middle Ages and Early Modern period is a relevant though insufficiently studied line of research. It is directly related to the issues of including these territories into the Russian state. However, in most cases the limited written and archaeological sources, characterizing the process of adoption of Islam by the local population, have led to the discussion adopting the same stereotyped plotlines. Most often, research has looked to characterize various possible factors possibly influencing the process of Islamization led by the representatives of Sufi tariqas, acting in the territory of the Shibanids within the ulus of Jochi, the Tyumen and Siberian Khanate in particular. A significant strengthening of the Muslims’ influence and their activity’s expansion is only revealed in the case of the last one. This process is automatically related to the Ugrian principalities connected with the Khanate, most often not in critical terms. At the same time, the analysis of chronicles mostly shows very limited possibilities of Islamic preaching outside the territory of various groups of Siberian Tatars. In such cases, preaching influenced either the representatives of the Ugrian elite alone, or reflected the domestic partnership of the Ugrians with Tatars. Under these conditions, the emergence of new approaches, which O.N. Naumenko and E.A. Naumenko claim in their works, force us to carefully analyze the proposed methods, sources, and results of the study of Islam among the West Siberian Ugrians. The work done in this regard shows that during the period under consideration, the adoption of Islam among the representatives of any groups of the Ob Ugrians would have been isolated incidents. As a rule, such episodes were connected with the elite of this society that was in close cooperation with the aristocracies of the Siberian Khanate. Dwelling in an interconnected way with the Turkic-Tatar population played a great role in this as well. Moreover, after the entry of Western Siberia into the Russian state, the number of such cases did not increase. On the contrary, sources define the Ostyaks and the Voguls as pagans. It is in this context that Orthodox preaching began among them.